MENAPAK TILAS KELISANAN DAN KEBERAKSARAAN DALAM KESUSASTERAAN ARAB PRA-ISLAM - Muhammad Walidin (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2014)
Abstract: This paper attempts to look at the tradition of orality in pre-Islamic Arabic literature based on the elements of the conceptual Ruth Finnegan on oral tradition and verbal art, namely Performance, Composition, and Transmission. In terms of performance, Arabic poetry grew from geographical conditions of the  Arabian Peninsula so that they make their communities in search of solace in the form of poetry. Poetry is displayed at various moments and each tribe has a poet certainly reliable. In terms of composition, Arabic poetry is an old literary tradition and the strongest. This tradition is able to form a system that is so strong convention. Until the 19th century, Arabic poetry systems are difficult to break away from this convention. Even now, it has not been fully able to break away from one aspect of this convention. From the aspect of the transmission, Arabic poetry submitted, either verbally or in writing just that it could be inferred from some clues that lead to the first option. Keywords: -Tradition, -Arabic literature, -Pre Islamic